Corporate communication as a substantial function in higher education management - ALPAYDIN, YUSUF (My University, 2022)
This study aims to reveal the benefits of corporate communication for higher education institutions. Within this scope, we address the areas that higher education systems are currently struggling with and discuss the factors that force institutions to change in light of the literature. In these circumstances that force higher education systems to change, we analyzed the need for well-planned communication studies for higher education institutions. We present evaluations on the potential impact of corporate communication efforts on the performance and success of higher education institutions, which have a wide stakeholder ecosystem. We determined the advantages that corporate communication provide to higher education management in the dimensions of basic management processes such as decision making, planning, organization, coordination, control, and evaluation.

Bu çalışmada kurumsal iletişimin yükseköğretim kurumları açısından faydalarının ortaya konması amaçlanmaktadır. Bu kapsamda yükseköğretim sistemlerinin mevcut mücadele alanlarına değinilmiş, kurumları değişime zorlayan faktörler literatür ışığında ele alınmıştır. Yükseköğretim kurumları için plan ve program dahilinde yürütülecek iletişim çalışmalarına yükseköğretim sistemlerini değişime zorlayan bu şartlarda ne denli ihtiyaç olduğunun tahlili yapılmaya çalışılmıştır. Kurumsal iletişim çalışmalarının çok geniş paydaş çevrelerine sahip olan yükseköğretim kurumlarının performans ve başarısı üzerinde potansiyel etkisi üzerine değerlendirmelerde bulunulmuştur. Temel yönetim süreçlerinden karar verme, planlama, örgütleme, eşgüdüm, kontrol ve değerlendirme boyutlarıyla kurumsal iletişimin yükseköğretim yönetimine sağladığı avantajlar belirlenmeye çalışılmıştır.
Yükseköğretim yönetiminde önemli bir fonksiyon olarak kurumsal iletişim
Keywords: Education; educational administration; higher education; higher education administration; corporate communication; Eğitim; eğitim yönetimi; yükseköğretim; yükseköğretim yönetimi; kurumsal iletişim